The Walking Whales : From Land to Water in Eight Million Years - Thewissen, J. G. M. (University of California Press, 2014)
Hans Thewissen, a leading researcher in the field of whale paleontology and anatomy, gives a sweeping first-person account of the discoveries that brought to light the early fossil record of whales. As evidenced in the record, whales evolved from herbivorous forest-dwelling ancestors that resembled tiny deer to carnivorous monsters stalking lakes and rivers and to serpentlike denizens of the coast. Thewissen reports on his discoveries in the wilds of India and Pakistan, weaving a narrative that reveals the day-to-day adventures of fossil collection, enriching it with local flavors from South Asian culture and society.